Efisiensi Pengelolaan Zakat dalam Tinjauan Fatwa Majelis Ulama Indonesia - Novendi Arkham Mubtadi; Dwi Vera Usmadyani; Farah Annisa (Universitas Wahid Hasyim Semarang, 2021)
This research analyzes where the Fatwa of the Indonesian Ulama Council (MUI) Number 8 of 2011 concerning Amil Zakat is implemented. The focus of the research is on increasing or not operating costs from the Regional Budget and Expenditure (APBD) assistance for amil provided by local governments after the issuance of the fatwa. This discusses increasing the efficiency of collecting and distributing zakat funds. The samples used were the National Zakat Amil Agency (BAZNAS) Banjarnegara Regency, Kebumen, and Purbalingga with a series of times from 2011 to 2015 using saturated samples, using all samples as samples. Showing, the three District BAZNAS that have been sampled have implemented the MUI Fatwa Number 8 of 2011 concerning Amil Zakat with the amount of APBD assistance for operational costs which increased sharply after the MUI fatwa. This was also followed by the amount collected and the distribution of large zakat funds efficiently. The suggestion for the next researcher is to be able to discuss operational costs towards efficiency and distribution of zakat with regression analysis so that the results obtained become more valid and reliable, by adding samples not only to three regencies and adding a series of time not only five years.